Human milk-derived versus bovine milk-derived fortifier use in very low birth weight infants: growth and vitamin D status - Lavassani, Emmanuelle; Tauber, Kate A.; Cerone, Jennifer B.; Ludke, Jennifer; Munshi, Upender K. (Frontiers in Pediatrics, 2024)
Background Human milk-derived fortifier (HMDF) coupled with human milk feeding in extremely premature infants reduces the adverse outcome risks of early exposure to bovine milk ingredients but may not provide enough nutrients for adequate catch-up growth compared with bovine milk-derived fortifier (BMDF). Objective This study aims to compare HMDF and BMDF effects on growth parameters and serum 25-hydroxy vitamin D (25OHD) levels in preterm very low birth weight (VLBW) infants during the first 8 weeks of life. Methods We present a retrospective chart review of inpatient VLBW infants with birth weight <1,500 g and gestational age <32 completed weeks who received either their mother’s milk or donor breast human milk fortified with HMDF or BMDF for the first 8 weeks. Weight, head circumference, length gain, and 25OHD level were calculated at 4 and 8 weeks of age. Results A total of 139 VLBW infants (91 HMDF + 48 BMDF) received fortified human milk without any supplemental premature formula from birth to 4 weeks of age, of whom 44 (37 HMDF + 7 BMDF) continued until 8 weeks of age. There was no statistically significant difference in the growth parameters between the two groups at 4 and 8 weeks of age. Serum 25OHD level in the HMDF group was significantly higher compared with that in the BMDF group at 4 weeks of age despite receiving lower vitamin D supplementation. Conclusion Similar gain in growth parameters in HMDF and BMDF groups at 4 and 8 weeks of age was observed, suggesting that HMDF provides adequate nutrients for growth in VLBW infants. A higher 25OHD level in HMDF may suggest better absorption.